2014
DOI: 10.1002/cncr.28662
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 and BRCA2 germline mutations are frequently demonstrated in both high‐risk pancreatic cancer screening and pancreatic cancer cohorts

Abstract: Background Ten percent of pancreatic ductal adenocarcinoma (PDAC) is due to genetic predisposition, including the breast and ovarian cancer syndrome germline mutations BRCA1 and BRCA2. Knowledge of specific genetic mutations predisposing to PDAC may enable risk stratification, early detection and development of effective screening and surveillance programs. We aimed to determine the diagnostic yield of testing for BRCA1/2 germline mutations in a PDAC screening cohort and a PDAC cohort referred for genetic test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 30 publications
0
48
0
2
Order By: Relevance
“…36, 37 Those factors, however, contribute less to pancreatic cancer on a population level, 38 and are unlikely to have major impact on worldwide mortality trends.…”
Section: Discussionmentioning
confidence: 99%
“…36, 37 Those factors, however, contribute less to pancreatic cancer on a population level, 38 and are unlikely to have major impact on worldwide mortality trends.…”
Section: Discussionmentioning
confidence: 99%
“…The cohort was significantly enriched with germline BRCA2 mutation in 17.2% of the patients while no germline mutations in the other three genes were observed (MP2K4, MADH4 and ACVR1B) (44). A similar study by Lucas and colleagues identified germline BRCA1/2 mutations in 21.9% of 32 patients with pancreatic cancer and 18.9% in patients without a cancer diagnosis currently enrolled in their high-risk pancreatic cancer prevention and genetics program (45). However, the majority of these early studies were significantly restricted by small sample size.…”
Section: Brca1/2 Mutations In Pancreatic Adenocarcinoma-tip Of the Icmentioning
confidence: 97%
“…It was found that BRCA2 mutation poses an increased risk for developing pancreatic cancer [20]. Some study proposed BRCA2 as a genetic factor as causes of the pancreatic cancer [21]. As like breast cancer, 5-10% of pancreatic cancer cases are believed to be hereditary.…”
Section: Brca1 and Brca2 Mutation In Pancreatic Cancer: Significancementioning
confidence: 99%